PENGUATAN TATA KELOLA MEDIA PUBLIKASI ASSURYANIYAH ISLAMIC CENTER CIMUNING, BEKASI, JAWA BARAT - Herfan, Djony; Pratiwi, Nurul Intan; Arifin, Zaenal (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2022)
Publication media is an important approach to promoting educational institutions. Therefore, community service to empower public relations for schools is carried out by the publishing study program (Journalism) of the Politeknik Negeri Jakarta to the Assuryaniyah Islamic Center Foundation. This activity is beneficial for teachers and administrative staff. Training materials are provided to teachers and administrative staff. There is a certain amount of information and communication that is difficult to convey. Therefore, teachers and staff receive training from experienced lecturers in the Journalism department. This activity is not only useful for establishing family relationships between Islamic boarding school institutions and the community but also empowers the management of communication media for educational institutions, web content packaging, and social media marketing, equipped with an understanding of various media legal issues. Thus, publication media owned by the Assuryaniyah foundation in the form of social media, such as Instagram, Facebook, and YouTube are more empowered to increase publications through social media. Teachers and administrative staff are involved as the foundation's social media is constantly well managed to make an impact on the Assuryaniyah foundation. Hence, students, parents, and the public can find out the dissemination of information, socialization, achievements, extracurricular activities, and promotion of the foundation carefully and precisely, and meticulously.Keywords: Media publications, information dissemination, teachers and administrative staff AbstrakMedia publikasi merupakan sarana mempromosikan lembaga pendidikan bagi masyarakat. Karena itu, kegiatan pengabdian kepada masyarakat berupa pelatihan pemberdayaan kehumasan bagi sekolah dilakukan oleh program studi penerbitan (Jurnalistik) kepada Yayasan Assuryaniyah Islamic Center. Kegiatan ini bermanfaat untuk guru-guru dan staf administrasi. Materi pelatihan yang diberikan kepada guru-guru dan staf administrasi. Ada sejumlah informasi dan komunikasi yang sulit disampaikan. Karena itu, guru-guru dan staf mendapat pelatihan dari pengajar berpengalaman di jurusan Jurnalistik. Kegiatan ini bukan hanya bermanfaat untuk menjalin hubungan kekeluargaan antara lembaga pondok pesantren dan masyarakat, melainkan juga memberdayakan pengelolaan media komunikasi untuk lembaga pendidikan, pengemasan konten web, pemasaran media sosial, dilengkapi dengan pemahaman pelbagai persoalan hukum media. Dengan demikian, media publikasi yang dimiliki oleh yayasan Assuryaniyah dalam bentuk media sosial, seperti instagram, facebook, dan youtube lebih diberdayakankebermanfaatannya untuk meningkatkan publikasi melalui media sosial. Guru-guru dan staf administrasi dilibatkan karena media sosial yayasan terus-menerus dikelola dengan baik untuk memberikan dampak bagi yayasan Assuryaniyah. Jadi, peserta didik, orang tua, dan masyarakat dapat mengetahui penyebaran informasi, sosialisasi, prestasi, kegiatan ekstrakurikuler, dan promosi yayasan secara cermat dan tepat serta teliti. Kata kunci: Publikasi media, penyebaran informasi, guru dan staf administrasi